Fear of Falling in Patients with Chronic Stroke: Differences of Functional Gait and Balance Measures According to the Level of Concern about Falling - Mania Sheikh; Hossein Asghar Hosseini (Shiraz University of Medical Sciences, 2016)
Background: In this study we investigated the differences of functional gait and balance measures between patients with chronic stroke with different level of concern about falling. Methods: Fifty-four patients with chronic stroke participated in this observational, cross-sectional study. The level of concern relating to falls was assessed by using the Falls Efficacy Scale-International. Thirty-three patients were classified as slightly concerned about falling, while twenty-one patients were highly concerned. Patients performed functional gait and balance tests including Berg Balance Scale, Timed Up & Go test, 10 Meter Walking Test and Functional Gait Assessment. The difference in outcome measures between the two groups was determined by an independent t-test. Results: All functional gait and balance tests of patients with high concern about falling were poorer than those for patients with slight concern. Conclusion: The level of concern relating to falls may influence gait and balance performance in individuals with chronic stroke and should be addressed in traditional gait and balance rehabilitation programs.